Influence Of Perceived Behavior Control Towards The Intention Of Dietary Behavior In Overweight Women - Ratih, Poppy Dwi; Hadjam, Noor Rochman; Maria, Ria; Karmilasari, Karmilasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the influence of perceived behavior control on dietary behavior intentions. Data collection techniques in this study were carried out through questionnaires and literature studies. The population in this study was overweight people in several regional public hospitals in Jakarta, while samples were determined by telknik purposive sampling. The results showed that perceived behavior control over dietary behavior intentions was influential and significant. The greater a person has a sense of ability and control in carrying out these behaviors, the stronger the intention of one's diet behavior. In the context of diet, a person with strong dietary behavioral intentions tends to feel more confident and able to better control his food consumption. This can affect a person's overall dietary behavior and help achieve desired dietary goals